2020
DOI: 10.3892/ijmm.2020.4461
|View full text |Cite
|
Sign up to set email alerts
|

Silencing CDC25A inhibits the proliferation of liver cancer cells by downregulating IL‑6 in�vitro and in�vivo

Abstract: cell division cycle 25A (cdc25A) is a core regulator of the cell cycle that has a dual-specific phosphatase activity, which is closely associated with the occurrence and development of a tumor, and is overexpressed in liver cancer. However, the molecular mechanism of cdc25A in the development of liver cancer remains unclear. The purpose of the present study was to further investigate the effect of cdc25A on cell proliferation in vitro and in vivo and to investigate whether an interaction exists between cdc25A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The up-regulation of REPS2 is associated with nuclear DKK-1 expression and is correlated with decreased OS in colorectal cancer ( Aguilera et al, 2015 ). Silencing CDC25A significantly inhibits the proliferation of liver cancer cells in vitro and in vivo ( Chen et al, 2020 ). The overexpression of GPR19 can regulate E-cadherin expression and invasion of breast cancer cells ( Rao & Herr, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of REPS2 is associated with nuclear DKK-1 expression and is correlated with decreased OS in colorectal cancer ( Aguilera et al, 2015 ). Silencing CDC25A significantly inhibits the proliferation of liver cancer cells in vitro and in vivo ( Chen et al, 2020 ). The overexpression of GPR19 can regulate E-cadherin expression and invasion of breast cancer cells ( Rao & Herr, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Six miRNAs ( miRNA-7-1, miRNA-17, miRNA-183, miRNA-210, miRNA-219a-1, and miRNA-942 ) and 5 miRNA modulators ( CDC25A , CDCA5 , E2F1 , EZH2 , and KIF23 ) were found to be significantly correlated with MEF2 expression and have a prognostic impact on GC patients. CDC25A is a member of the cell division cycle 25 family, which has been reported to be overexpressed in a wide range of cancer types and associated with cancer cell survival and tumor growth ( 31 - 34 ). Unlike some previous studies ( 35 - 37 ), we found that overexpression of CDC25A could prolong GC survival.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are soluble extracellular mediators such as chemokines, IFN, interleukins (IL), lymphokines, and tumor necrosis factors, which have important roles in immune response activation. IL-6 is a pleiotropic cytokine that regulates hematopoiesis and immune and inflammatory responses and contributes to T and B cell activation, proliferation, and differentiation (Chen et al, 2020). IL-8, also known as CXCL8, is an important immune response mediator produced by macrophages and peripheral blood mononuclear cells (Zou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%